(untitled) (Research, Society and Development, 2025)
Aromatherapy is an integrative practice recognized by the National Policy on Integrative and Complementary Practices, which uses essential oils to promote physical, mental, and emotional balance. The general objective was to analyze the effects of aromatherapy in reducing stress and improving the psychological well-being of these professionals. The methodology consisted of an extension activity with a qualitative and descriptive approach, in which lavender, lemongrass, and mandarin aromas were used during a sensory experience circle and direct observation of participants’ reactions. This study is limited to the application of this practice as a health promotion strategy among military police officers of the Northern Area Command in Manaus. The results indicated reduced anxiety, improved mood, a sense of relaxation, and strengthened interpersonal relationships. It is concluded that aromatherapy can be incorporated as a complementary practice in occupational health, promoting quality of life and emotional balance among police officers.